HOUT-22. EVALUATING CLINICAL IMPACT UTILIZING THE RANO-PRO COLLABORATIVE'S STANDARDIZED PRIORITY CONSTRUCTS. (11th November 2019) - Vera, Elizabeth; Gilbert, Mark; Aboud, Orwa; Antony, Ramya; Boris, Lisa; Bryla, Christine; Burton, Eric; Cordova, Christine; Crandon, Sonja; Leggiero, Nicole; Penas-Prado, Marta; Reyes, Jennifer; et al.
Abstract: Increasing recognition of the symptom burden and functional limitations among primary brain tumor (PBT) patients has led to proposing clinical outcomes assessments as an additional measure of a treatment's effectiveness. The RANO-PRO Collaborative recommended core symptoms for evaluation in clinical care and research for malignant glioma are weakness, walking, seizures, communication, memory, and treatment-specific symptoms. We evaluated these symptoms using the MDASI-Brain Tumor (BT) in the PBT patient sample of the NCI-NOB Natural History Study, in relation to disease progression, by descriptive statistics, and independent- and paired-samples t-tests. The sample included 434 PBT patients (59% male, median age=50 (18–83), 82% white, 43% with a prior recurrence). In the 60% with a malignant glioma, weakness, walking, seizures, difficulty remembering, and fatigue were significantly worse in the group with progression at time of imaging compared to the group with stable disease ( p < 0.05). In a subset of 114 patients with progression after study entry, reported severity in all symptoms (except seizures) significantly worsened from study entry to time of progression (-1.7< mean difference< -0.1, p < 0.02, 0.3< r < 0.5). Walking, weakness, difficulty remembering, and fatigue each had a difference greater than 1-point, the minimally important difference for MDASI-BT. No one core symptom accounted for the severity change; each was reported by 17%-35% of patients as their largest change in severity. Utilizing the symptom with the largest change increased the magnitude of the worsening and its effect size (mean difference=-2.9, r =0.5). The analysis was repeated in the larger PBT sample with similar statistical findings but with smaller mean differences. RANO-PRO Collaborative core symptoms were shown to worsen at time of progression on imaging, highlighting the importance of continual symptom assessment and validating this core symptom group. Further analysis will focus on degree of change with each core symptom and validation in other datasets.